Using Celecoxib for the Suppression of Preterm Labor Instead of Magnesium Sulfate - Najmieh Saadati; Farideh Moramezi; Maria Cheraghi; Laila Sokhray (Journal of Pregnancy)
We aimed to use celecoxib to suppress preterm labor instead magnesium sulfate (MgSO4) to prevent preterm labor. Methods. It was a randomized clinical trial study, which was done on 600 pregnant women. All subjects were divided into two groups by simple random sampling. One group was given 4 grams of MgSO4 intravenously and second group was given 100 mg of celecoxib orally every 12 hours for at least 2 days. The data were entered and analyzed using SPSS 11 and performed using t-test and chi-square test. Results. The finding of this study has shown that preterm labor may be prevented in 75.7% of subjects who had received celecoxib and there were no significant difference between two groups in frequency of history of preterm labor (P=1), frequencies of nulliparity (P=0.99), duration of drug use and arrest contraction (P=0.29), delivery before 48 hours (P=0.20), and mean gestational age in lack of response to treatment (P=0.24). Conclusions. Result has shown that celecoxib was similar to MgSO4 as a medication to prevent preterm labor; it was recommended to be prescribe to prevent preterm labor, because it was cheaper than magnesium sulfate.